Updates on the taxonomy and nomenclature of Australian Sarcophaga (sensu lato) (Diptera: Sarcophagidae), with descriptions of two new species - Meiklejohn, Kelly A; Wallman, James F; Pape, Thomas (Zootaxa, 2013)
Two new species, Sarcophaga (Sarcosolomonia) collessi sp.nov. and Sarcophaga (Sarcorohdendorfia) clavus sp.nov., both collected in Queensland, Australia, are described, and the following four new synonymies are proposed: Sarcophaga horti Blackith and Blackith, 1988 syn.nov. of Sarcophaga bancroftorum Johnston and Tiegs, 1921; Sarcophaga fergusoni-na Hardy, 1940 syn.nov. of Sarcophaga assimilis Macquart, 1851; Sarcophaga brevicornis Ho, 1934 syn.nov. of Sar-cophaga kohla Johnston and Hardy, 1923a; and Sarcophaga triplex Hardy, 1943 syn.nov. of Sarcophaga furcata Hardy, 1932.